2020
DOI: 10.1016/j.neuro.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Decreased viability and neurite length in neural cells treated with chitosan-dextran sulfate nanocomplexes

Abstract: CXCL12 is a chemokine known to regulate migration, proliferation, and differentiation of neural stem cells (NSCs) and to play a neuroprotective role in ischemic stroke. Chitosan-dextran sulfate nanocomplexes (Ch/DS NC) are known nanoparticulated systems used to efficiently deliver heparin-binding factors. Here we evaluate Ch/DS NC as carriers for CXCL12 in a mouse model of stroke. Free CXCL12 reduced the size of the ischemic brain lesion. However, when Ch/DS NC were administrated, the stroke volume increased. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…We observed that CHI negatively affected neuronal maturation but instead allowed the development of astrocytes at a higher ratio (Figure 4M). Similar outcomes were observed in previous CNS reports where CHI nanoparticles as a drug delivery system reduced neuronal viability and neurite extension while impairing neural stem cell migration [80]. This effect could be attributed to the high charge density of CHI, creating a proneuroinflammatory environment that damages neurons but supports glial cells [81].…”
Section: Discussionsupporting
confidence: 86%
“…We observed that CHI negatively affected neuronal maturation but instead allowed the development of astrocytes at a higher ratio (Figure 4M). Similar outcomes were observed in previous CNS reports where CHI nanoparticles as a drug delivery system reduced neuronal viability and neurite extension while impairing neural stem cell migration [80]. This effect could be attributed to the high charge density of CHI, creating a proneuroinflammatory environment that damages neurons but supports glial cells [81].…”
Section: Discussionsupporting
confidence: 86%
“…Whatever the type of cell death, these guidelines describe the rearrangements that cytoskeletal dynamics could undergo (Kroemer et al, 2008;Galluzzi et al, 2018;Ren et al, 2021). Although the absence of cytotoxicity is a general feature of CS-NCs, in some specific systems, such as tumoral cells, death pathways are triggered (Venkatesan et al, 2011;Taranejoo et al, 2016;Zamproni et al, 2020) (Fig. 1).…”
Section: Chitosan-based Ncs Uptake and Its Impact On The Cytoskeleton Dynamicsmentioning
confidence: 99%
“…Y. Chen was the first to fabricate and entrap an arginine-rich hexapeptide into CS-DS nanoparticles [22]. This increased the popularity of biopolymer-based nanoparticle research and led to further developments in the field such as the encapsulation of insulin into CS-based nanoparticles [23,24].…”
Section: Introductionmentioning
confidence: 99%